Preface to the Special Issue “Algebraic Structures and Graph Theory” - Irina Cristea; Hashem Bordbar (Mathematics, 2023)
Connections between algebraic structure theory and graph theory have been established in order to solve open problems in one theory with the help of the tools existing in the other, emphasizing the remarkable properties of one theory with techniques involving the second [...]